A late Carboniferous bimodal volcanic suite before closure of the North Tianshan Ocean at the southwestern margin of the Central Asian Orogenic Belt. (1st April 2022) - Xie, Wei; Lu, Yin; Song, Xie-Yan; Deng, Yu-Feng; Liang, Qing-Lin; Yi, Jun-Nian
Graphical abstract: Highlights: The previously thought Permian volcanic rocks are formed in 318–311 Ma. The LREE-poor and -rich basalts and andesites were formed via different mechanisms. The I-type rhyolites were derived from anatexis of old arc crustal rocks. The Yamanu volcanic arc was a forearc system during the late Carboniferous. Abstract: The North Tianshan Ocean (NTO) was one of the youngest oceanic basins at the southwestern margin of the Central Asian Orogenic Belt. When, where and how the NTO was finally consumed and closed have not been well addressed. To better understand the tectonic evolution of the NTO, particularly before its closure, an integrated study of volcanic rocks in the Yamansu volcanic arc has been carried out. Two SHRIMP zircon U–Pb ages (317.6 ± 3.1 Ma and 310.7 ± 2.4 Ma) indicate that the previously identified Permian volcanic rocks erupted during the late Carboniferous instead. The late Carboniferous volcanics in the region are composed of a bimodal suite with a SiO2 compositional gap between 60 and 70%. The mafic volcanics could be further divided into LREE-poor basalts and LREE-rich basalt-andesites. The LREE-poor variety displays tholeiite and forearc-like characteristics with flat to depleted LREE patterns with (La/Yb)N  < 1.5, which were likely derived from a moderately depleted mantle wedge metasomatized by a subducted fluid-like component. The LREE-rich suite is calc-alkaline and has enriched LREE patterns with high (La/Yb)N  > 2. They were from a depleted mantle wedge metasomatized by subducted sediment-derived melts, although more or less suffered crustal contamination. The felsic volcanics are I-type rhyolites, derived from anatexis of Cambrian to Mesoproterozoic arc crustal rocks. Here, we suggest that the Kanggur Fault presumably represented the southernmost suture of NTO. The Yamansu volcanic arc was a forearc system of the Central Tianshan continental arc related to southward subduction of the NTO.